外大陆架划界中的不确定因素及其在北极的国际实践 - 桂静; Gui Jing (《中国海洋法学评论》编辑部, 2010)
桂静,女,硕士,国家海洋信息中心副研究员,研究方向:海洋情报与海洋权益管理。电子邮箱:jingui59167@yahoo.com.cn 北极地区的争夺正经历着从科学考察向争夺资源的转变,且目前集中于外大陆架划界和航道方面。有关外大陆架界限的《联合国海洋法公约》第 76条具有不确定性。它为相关国家主张权利提供依据的同时,也造成利用国之间的争端。客观地讲,公约内容也需要这样的国际实践对其不确定性加以丰富和确认。因此,联合国大陆架界限委员会的处理意见不仅对北极地区类似争端的解决,而且对全世界都将会有重要意义。我国对北极存在海洋利益,应当重视此问题并采取相应策略。 Disputes over the Arctic are shifting from those regarding scientific research to those over entitlement to resources.These disputes currently focus on delimitation of the outer continental shelf and navigational channels. Provisions related to the outer continental shelf boundaries in Article 76 of the UN Convention on the Law of the Sea are uncertain.While these provisions provide the basis for surrounding countries’claims to certain rights in the region,they also are the source of disputes among these countries.Objectively speaking,it is necessary to address the uncertainty of the Convention through international practice.Therefore,opinions rendered by the UN Commission on the Limits of the Continental Shelf will have vital significance for theresolution of similar conflicts not only in the Arctic,but also in the rest of the world.As a country with existing interests in the Arctic,China should examine the seopinions closely and respond accordingly.